Graphite negative electrode material coated with artificial SEI (solid electrolyte interface) film as well as preparation method and application of graphite negative electrode material

By forming an artificial SEI film and a polymer cladding layer doped with graphene on the surface of the graphite, the first Coulomb efficiency and rate performance problems of graphite negative electrode materials are solved, and the performance improvement of high-efficiency and low-cost lithium-ion battery is achieved.

CN120413650APending Publication Date: 2025-08-01HENAN ZIBEN NEW ENERGY TECH CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510661771.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-22
Publication Date
2025-08-01

AI Technical Summary

Technical Problem

The existing graphite anode materials have low Coulomb efficiency, poor rate performance for the first time in lithium-ion batteries, and amorphous carbon coating leads to problems of high cost and low first-term efficiency.

Method used

Through oxidative etching and doping coating technology, an artificial SEI film is formed on the graphite surface, and a porous structure is formed by oxidative etching, and a polymethyl methacrylate coating layer doped with graphene is formed thereon, improving binding stability and electrical conductivity.

Benefits of technology

It significantly improves the first-time efficiency and rate performance, reduces electrolyte consumption, improves the efficiency of positive electrode usage, reduces battery costs, and reduces the cost by more than 30% compared with amorphous carbon coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120413650A_ABST
    Figure CN120413650A_ABST
Patent Text Reader

Abstract

The invention discloses an artificial SEI film coated graphite negative electrode material and a preparation method and application thereof, and belongs to the technical field of lithium ion battery negative electrode materials. The preparation method comprises the following steps: heating and oxidizing graphite in mixed gas of air and nitrogen, and cooling to obtain oxidized and etched graphite; then dispersing the oxidized and etched graphite in a solvent, adding methyl methacrylate and graphene, stirring and initiating an in-situ polymerization reaction, and forming a doped coating layer on the oxidized and etched graphite; and finally, carrying out vacuum drying on the coated oxidized and etched graphite, and cooling to obtain the artificial SEI film coated graphite negative electrode material. The specific surface area of graphite is increased through oxidation etching, the ion diffusivity is improved, the combination effect of the organic polymer is improved, the first efficiency of the negative electrode material is remarkably improved by combining the synergistic effect of the conductive polymerized organic matter and graphene, and the conductivity, the structural stability and the interface compatibility are enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of anode materials for lithium-ion batteries, and specifically relates to a graphite anode material coated with an artificial SEI film, its preparation method, and applications. Background Art

[0002] As an anode material for lithium-ion batteries, graphite has the advantages of low cost and good stability. However, problems such as its low initial coulombic efficiency (usually <90%) and poor rate performance limit its application in fast-charging batteries.

[0003] Currently, the mainstream solution is to coat amorphous carbon on the surface of graphite to improve rate performance. However, the coating of amorphous carbon brings problems of high cost and low initial efficiency. This low initial efficiency not only reduces the capacity density of lithium-ion batteries but also reduces the utilization efficiency of high-cost cathodes.

[0004] In recent years, artificial SEI (solid electrolyte interface) film technology has attempted to improve the interface performance by pre-coating a functional layer and to increase the initial efficiency and cycle efficiency of anode materials by reducing the side reaction between the electrolyte and graphite. However, due to the hydrophobic organic characteristics of untreated graphite materials and the relatively high organic content of artificial SEI films compared to self-generated SEI films, which reduces the electronic conductivity, etc., existing methods generally have problems such as poor adhesion between the coating layer and graphite, uneven coating, insufficient conductivity, and high cost. Summary of the Invention

[0005] The technical problem to be solved by the present invention is to provide a graphite anode material coated with an artificial SEI film, its preparation method, and applications, and to obtain a graphite anode material with high initial efficiency and high rate performance through oxidation etching and doping coating technology.

[0006] To solve the above technical problems, according to one aspect of the present invention, provided is a preparation method of a graphite anode material coated with an artificial SEI film, including: Step 1, heating and oxidizing graphite in a mixed gas of air and nitrogen, and obtaining oxidized and etched graphite after cooling; Step 2, dispersing the oxidized and etched graphite in a solvent, adding methyl methacrylate and graphene, stirring and initiating an in-situ polymerization reaction to form a poly(methyl methacrylate) coating layer doped with graphene on the oxidized and etched graphite; Step 3, vacuum-drying the coated oxidized and etched graphite, and obtaining a graphite anode material coated with an artificial SEI film after cooling.

[0007] Further, in Step 1, in the mixed gas, the volume ratio of air to nitrogen is 1:1 - 6:1.

[0008] Further, in Step 1, the heating and oxidation temperature is 200 - 450 °C.

[0009] Further, in Step 1, the graphite is selected from one or more combinations of natural graphite, artificial graphite, carbon-coated natural graphite, and carbon-coated artificial graphite.

[0010] Further, in Step 2, the addition amount of methyl methacrylate is 2-20% of the mass of the graphite.

[0011] Further, in Step 2, the addition amount of graphene is 0.2-5% of the mass of the graphite.

[0012] Further, in Step 2, azobisisobutyronitrile (AIBN) is added to initiate an in-situ polymerization reaction.

[0013] Further, in Step 3, the temperature of vacuum drying is 90±5°C.

[0014] According to another aspect of the present invention, provided is a graphite negative electrode material coated with an artificial SEI film obtained by the above preparation method.

[0015] According to another aspect of the present invention, provided is the application of the graphite negative electrode material coated with the artificial SEI film as described above in the preparation of a negative electrode of a lithium-ion battery.

[0016] The present invention improves the specific surface area of graphite through oxidative etching, not only improving the ion diffusion ability, but also enhancing the binding effect between the organic polymer and graphite. Combining the synergistic effect of conductive polymer organic matter and graphene significantly improves the first efficiency of the negative electrode material, enhances the conductivity, structural stability, and interfacial compatibility.

[0017] For the material obtained according to the present invention, (1) the first Coulomb efficiency > 91%, and under further optimized conditions, the first Coulomb efficiency can reach more than 95%, which can reduce the consumption of the electrolyte, improve the utilization efficiency of the positive electrode, and reduce the battery cost; (2) the charging capacity at 6C rate > 87%, and can reach more than 95% under further optimized conditions; (3) the cost is reduced by more than 30% compared with the coated amorphous carbon negative electrode with the same rate performance. Description of the Drawings

[0018] Figure 1 is a schematic diagram of the preparation process of Example 1; Figure 2 is a scanning electron microscope image (SEM) of artificial graphite before (a) and after (b) oxidative etching in Example 1; Figure 3 is a transmission electron microscope image (TEM) of artificial graphite coated with an artificial SEI film in Example 1; Figure 4 is the first charge-discharge curve of the material obtained in Example 1. Detailed Embodiments

[0019] A typical implementation of the present invention provides a method for preparing a graphite anode material coated with an artificial SEI film. The basic concept is as follows: graphite is oxidized and etched to form graphite oxide; the graphite oxide, methyl methacrylate, and graphene are uniformly dispersed in a liquid phase, and a uniform composite coating layer is formed through in-situ polymerization and doping coating; finally, heat treatment and drying are performed to obtain the graphite anode material coated with the artificial SEI film. The preparation method includes the following steps 1 to 3.

[0020] Step 1: Heat and oxidize graphite in a mixed gas of air and nitrogen, and obtain oxidized and etched graphite after cooling. Porous structures can be formed on the graphite surface through oxidation and etching to increase active sites.

[0021] In the mixed gas, the ratio of air to nitrogen (volume ratio) is preferably 1:1 - 6:1. Exemplarily, the ratio of air to nitrogen is 1:1, 2:1, 3:1, 4:1, 5:1, or 6:1.

[0022] In this step, the heat oxidation temperature is 200 - 450 °C. Exemplarily, the heat oxidation temperature is 200 °C, 250 °C, 300 °C, 350 °C, 400 °C, 450 °C.

[0023] The use of the mixed gas can achieve low-cost and controllable oxidation of the graphite material to form the oxidized and etched graphite.

[0024] Preferably, the graphite is selected from one or a combination of two or more of natural graphite, artificial graphite, carbon-coated natural graphite, and carbon-coated artificial graphite.

[0025] Step 2: Disperse the oxidized and etched graphite in a solvent, add methyl methacrylate and graphene, stir and initiate an in-situ polymerization reaction to form a poly(methyl methacrylate) coating layer doped with graphene on the oxidized and etched graphite.

[0026] Poly(methyl methacrylate) has excellent electronic conductivity and ionic conductivity characteristics. Introducing poly(methyl methacrylate) on the surface of graphite oxide and synchronously doping graphene helps enhance electron conduction and mechanical stability.

[0027] In this step, azobisisobutyronitrile (AIBN) is added to initiate the in-situ polymerization reaction, and poly(methyl methacrylate) is generated in the reaction. Preferably, the addition amount of azobisisobutyronitrile (AIBN) is 2% of the mass of methyl methacrylate.

[0028] More specifically, after adding methyl methacrylate and graphene, they are ultrasonically dispersed evenly and then stirred and heated to 65 °C, and then the above-mentioned azobisisobutyronitrile (AIBN) is added to initiate the in-situ polymerization reaction.

[0029] Among them, the addition amount of methyl methacrylate is 2-20% of the mass of graphite. Exemplarily, the addition amounts of methyl methacrylate are 2%, 5%, 10%, 15%, and 20% of the mass of graphite.

[0030] Among them, the addition amount of graphene is 0.2-5% of the mass of graphite. Exemplarily, the addition amounts of graphene are 0.2%, 0.5%, 1%, 2%, 3%, 4%, and 5% of the mass of graphite.

[0031] The solvent described in this step is preferably absolute ethanol.

[0032] Step 3: Vacuum-dry the oxidized and etched graphite after coating, and obtain the graphite anode material coated with the artificial SEI film after cooling.

[0033] In this step, the vacuum drying is to heat to 90±5°C under vacuum in a vacuum drying oven for drying.

[0034] According to the above embodiments, by utilizing the unique electronic conductivity and ionic conductivity characteristics of polymethyl methacrylate, in-situ reaction points are formed on the surface of graphite through oxidation etching to improve the binding stability between the polymethyl methacrylate coating layer and graphite; at the same time, the doping of graphene is used to simultaneously improve the conductive effect and structural stability of the polymethyl methacrylate coating layer.

[0035] The following further illustrates the technical solutions claimed in the present invention through some embodiments. However, the embodiments and comparative examples are used to explain the implementation solutions of the present invention and do not exceed the scope of the present invention's theme. The protection scope of the present invention is not limited by the described embodiments. Unless otherwise specifically stated, the materials and reagents used in the present invention can be obtained from commercial products in the art. Example 1

[0036] Place 10 g of artificial graphite in a tube furnace, introduce a mixed gas of air and nitrogen with a volume ratio of 3:1, heat to 400°C and hold for 2 hours, and then cool to obtain oxidized and etched graphite.

[0037] Disperse the above oxidized and etched graphite in absolute ethanol, add 0.5 g of methyl methacrylate and 0.2 g of graphene, ultrasonically disperse evenly, then stir and heat to 65°C, add 2% of AIBN based on the mass of methyl methacrylate to initiate an in-situ polymerization reaction, and the reaction time is 30 min.

[0038] After cooling, heat the mixed solution to 90°C under vacuum in a vacuum drying oven for drying, and obtain the anode material after cooling.

[0039] Examples 2-12 Based on the preparation method provided in Example 1, the type of graphite, the ratio of air to nitrogen in the mixed gas, the oxidation temperature, and the mass of methyl methacrylate and graphene were adjusted. The specific parameters are shown in Table 1.

[0040] Comparative Example 1 Amorphous carbon was coated with natural graphite without oxidation and subsequent coating, and the material properties of the natural graphite-coated amorphous carbon were directly tested for comparison.

[0041] Comparative Example 2 Amorphous carbon was coated with artificial graphite without oxidation and subsequent coating, and the material properties of the artificial graphite-coated amorphous carbon were directly tested for comparison.

[0042] Table 1 Main preparation conditions for each example and comparative example

[0043] The specific surface area of the graphite oxide in Examples 1-12 was tested, and the electrochemical performance of the anode materials obtained in Examples 1-12 and Comparative Examples 1-2 was tested. The rate performance of some of the materials was tested by assembling 5 Ah laminated batteries.

[0044] The specific surface area of the graphite oxide prepared in Examples 1-12 was tested by nitrogen adsorption according to the BET method.

[0045] Using the materials prepared in the comparative examples and examples as the anode materials, they were mixed with the binder polyvinylidene fluoride (PVDF) and the conductive agent (Super-P) in a mass ratio of 80:10:10, and an appropriate amount of N-methylpyrrolidone (NMP) was added as a solvent to make a slurry, which was coated on a copper foil and then vacuum dried and roll-pressed to prepare an anode sheet. A lithium metal sheet was used as the counter electrode, and an electrolyte of 1 mol / L LiPF6 three-component mixed solvent mixed according to EC:DMC:EMC = 1:1:1 (v / v) was used. A polypropylene microporous membrane was used as the separator, and a CR2032 type button cell was assembled in a glove box filled with inert gas. The charge and discharge tests of the button cell were carried out on the battery test system of Wuhan Blue Electronic Co., Ltd. Under normal temperature conditions, constant current charge and discharge at 0.1C, and the charge and discharge voltage was limited to 0.005-1.5V to test the first discharge capacity and first discharge efficiency of the anode.

[0046] The following method was used to test and calculate the rate performance of the materials: The anode materials in the examples and comparative examples were applied to a soft-pack laminated battery with a nominal capacity of 5 Ah using lithium iron phosphate as the cathode. After the battery was assembled, formation and grading were carried out according to the normal system, and then charge and discharge were carried out at a current of 5 A. The charge capacity was marked as C1, and then charge and discharge were carried out at a current of 30 A. The charge capacity was marked as C6, and C6 / C1*100% = 6C charge ratio.

[0047] Table 2 Characterization of Material Physical and Electrochemical Properties of Each Example and Comparative Example

[0048] By comparison Figure 2 It can be found from the scanning electron microscopy of Example 1 before (a) and after (b) oxidative etching that after oxidative etching, the smooth and round surface morphology of graphite becomes rough, and the edge roughness increases. This etching is beneficial to improving the bonding stability between the artificial SEI layer and graphite.

[0049] By comparing Figure 3 It can be found from the transmission electron microscopy comparison of uncoated graphite and graphite coated with artificial SEI film in Example 1 that a uniform, continuous and smooth artificial SEI film coating layer can be obtained.

[0050] It can be found by comparing the data in Example 1 and Comparative Example 2 that compared with directly carbon coating artificial graphite, doping and coating artificial SEI film on artificial graphite increases the first efficiency from 93.2% to 95.6% and the 6C charging ratio from 86.7% to 95.7%. It can be found by comparing the data in Example 2 and Comparative Example 1 that a similar performance improvement is also obvious.

[0051] It can be found by comparing the data of Example 1 with those of Examples 5, 6, and 7 that optimizing the oxidative etching intensity of artificial graphite can significantly improve the first efficiency and rate performance, indicating that the in-situ activation points formed by oxidative etching have a prominent effect on promoting the stability of the polymer coating layer.

[0052] It can be found by comparing the data of Example 1 with those of Examples 9 and 10 that methyl methacrylate with an optimized ratio has an ideal effect on improving the first efficiency and rate performance, indicating that the contribution of methyl methacrylate to improving the first efficiency and rate performance is obvious.

[0053] It can be found by comparing the data of Example 1 with those of Examples 11 and 12 that the contribution of graphene with an optimized ratio to performance improvement; it can be found that the contribution of graphene with an optimized ratio to improving the first efficiency and kinetic performance is very prominent.

Claims

1. A preparation method of an artificial SEI film-coated graphite anode material, characterized in that Comprising: Step 1: Heat and oxidize graphite in a mixed gas of air and nitrogen, and obtain oxidized and etched graphite after cooling; Step 2: Disperse the oxidized and etched graphite in a solvent, add methyl methacrylate and graphene, stir and initiate an in-situ polymerization reaction to form a doped coating layer on the oxidized and etched graphite; Step 3: Vacuum-dry the coated oxidized and etched graphite, and obtain a graphite anode material coated with an artificial SEI film after cooling.

2. The preparation method of the artificial SEI film-coated graphite anode material according to claim 1, characterized in that: In Step 1, in the mixed gas, the volume ratio of air to nitrogen is 1:1 - 6:

1.

3. The preparation method of the artificial SEI film-coated graphite anode material according to claim 2, wherein: In Step 1, the heat oxidation temperature is 200 - 450 °C.

4. The preparation method of the artificial SEI film-coated graphite anode material according to claim 3, wherein: In Step 1, the graphite is selected from one or more combinations of natural graphite, artificial graphite, carbon-coated natural graphite, and carbon-coated artificial graphite.

5. The preparation method of the artificial SEI film-coated graphite anode material according to claim 1 or 4, characterized in that: In Step 2, the addition amount of methyl methacrylate is 2 - 20% of the mass of graphite.

6. The preparation method of the artificial SEI film-coated graphite anode material according to claim 5, wherein: In Step 2, the addition amount of graphene is 0.2 - 5% of the mass of graphite.

7. The preparation method of the artificial SEI film-coated graphite anode material according to claim 6, wherein: In Step 2, azobisisobutyronitrile (AIBN) is added to initiate an in-situ polymerization reaction.

8. The preparation method of the artificial SEI film-coated graphite anode material according to claim 1 or 7, characterized in that: In Step 3, the temperature of vacuum drying is 90 ± 5 °C.

9. A graphite anode material coated with an artificial SEI film obtained by the preparation method according to any one of claims 1 - 7.

10. Use of the graphite anode material coated with an artificial SEI film according to claim 9 in the preparation of an anode of a lithium-ion battery.

Citation Information

Cited By

  • Regenerated graphite negative electrode material, preparation method thereof, negative electrode and lithium ion battery

    CN121085261A

  • High-specific-surface-area negative electrode material based on CO2 etched microcrystalline graphite and preparation method of high-specific-surface-area negative electrode material

    CN122187032A